2021
DOI: 10.1101/2021.03.25.437073
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The von Willebrand Factor stamps Plasmatic Extracellular Vesicles from Glioblastoma Patients

Abstract: Glioblastoma is a devastating tumor of the central nervous system characterized by a poor survival and an extremely dark prognosis, making its diagnosis, treatment and monitoring highly challenging. Numerous studies have highlighted extracellular vesicles (EVs) as key players of tumor growth, invasiveness and resistance, as they carry and disseminate oncogenic material in the local tumor microenvironment and at distance. However, whether their quality and quantity reflect individual health status and changes i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A recent study showed the Videodrop to correctly enumerate two lentiviral virions and a baculovirus, whereas it underestimated the absolute viral concentration of an adenovirus relative to classical titration procedures (Turkki et al., 2021). A Videodrop instrument was also used to estimate the concentration of EVs in plasma, but no control experiments to verify the performance of the device were done in this study (Sabbagh et al., 2021). The main characteristics of the Videodrop, ZetaView, and NanoSight instruments are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed the Videodrop to correctly enumerate two lentiviral virions and a baculovirus, whereas it underestimated the absolute viral concentration of an adenovirus relative to classical titration procedures (Turkki et al., 2021). A Videodrop instrument was also used to estimate the concentration of EVs in plasma, but no control experiments to verify the performance of the device were done in this study (Sabbagh et al., 2021). The main characteristics of the Videodrop, ZetaView, and NanoSight instruments are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed the Videodrop to correctly enumerate two lentiviral virions and a baculovirus, whereas it underestimated the absolute viral concentration of an adenovirus relative to classical titration procedures (Turkki et al 2021). A Videodrop instrument was also used to estimate the concentration of EVs in plasma, but no control experiments to verify the performance of the device were done in this study (Sabbagh et al 2021). The main characteristics of the Videodrop, ZetaView, and NanoSight instruments are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%